2015
DOI: 10.1139/cjb-2014-0245
|View full text |Cite
|
Sign up to set email alerts
|

Developmental morphology and anatomy of the reproductive structures in sunflower (Helianthus annuus): a unified temporal scale

Abstract: In sunflower (Helianthus annuus L.) there has been an intense genetic selection for achenes with agronomic value, such as greater weight, oil content, and disease resistance.However, the information regarding the anatomical events that control their growth and maturation is surprisingly scarce.The aim of the present work was to study sunflower male and female sporogenesis and gametogenesis as well as cell division and enlargement and tissue differentiation in the ovary and the embryo, linking the timing of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…In our study, EXPN expression patterns suggest an earlier specific role (from − 12 to + 6 DFA) for EXPN7 and EXPN10 in the ovary and pericarp, respectively, compared with other isoforms. This agrees with Lindström and Hernández (2015) [ 51 ], who demonstrated that final pericarp size is attained at + 8 DFA when secondary wall deposition in the pericarp cells begins.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, EXPN expression patterns suggest an earlier specific role (from − 12 to + 6 DFA) for EXPN7 and EXPN10 in the ovary and pericarp, respectively, compared with other isoforms. This agrees with Lindström and Hernández (2015) [ 51 ], who demonstrated that final pericarp size is attained at + 8 DFA when secondary wall deposition in the pericarp cells begins.…”
Section: Discussionsupporting
confidence: 92%
“…Maximum pericarp water content was attained by + 10 DFA (Fig. 3 ), concurring with other studies [ 8 , 51 ] and reinforcing the link between EXPN expression and water dynamics of sunflower grains. In our study, EXPN expression patterns suggest an earlier specific role (from − 12 to + 6 DFA) for EXPN7 and EXPN10 in the ovary and pericarp, respectively, compared with other isoforms.…”
Section: Discussionsupporting
confidence: 91%
“…24 At that time achene filling in the peripheral flowers had begun. 25 At R8 all flowers had reached full development within the inflorescence.…”
Section: Flower Removal Experimentsmentioning
confidence: 99%
“…For each year and growing period, bars not sharing a common letter are significantly different at the .05 probability level filled grain number due to flower or developing embryo abortion (Egli, 1998;Lindström et al, 2006). Once filled grain number is fixed (Lindström & Hernández, 2015), adjustment in grain yield as consequence stress conditions could occur only through variation in grain weight. In our work, the higher moisture and thermal stress indices during the emergence to maturity period in 2013 than in 2012 (Table 1) reduced grain yield, filled grain number, and to a lesser extent weight per grain (Figure 2a).…”
Section: Filled Grain Numbermentioning
confidence: 99%